HAKEKAT RUMAH PADA PERENCANAAN RUMAH SUSUN - Wita Widyandini (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2012)
ABSTRACTA shocking news, there are 72 from 74 mansions in Indonesia stopped and abandoned by their occupants. Our question is, why does it happen? Is it because the uninteresting and unattractive home design or the home facilities that not capable to accommodate all the occupantâ€™s life needs?Â One certain thing should be noted by the developers of the mansion is that the occupants should feel comfortable on their mansion. Occupants should feels that the mansion is part of themselves, not just a place for live. So that, should understand the meaning of a house in a humanâ€™s life.Keywords: house essence, planning, mansion.